Impact of watershed interventions on soil fertility status in Bundelkhand region of semi-arid tropics, India - Kumar, Dhiraj; Prasad, Rajendra; Singh, Ramesh; Rizvi, R.H.; Chavan, S.B.; Dev, Inder; Dwivedi, R.P.; Tewari, R.K.; Ram, Asha; Kumar, Sudhir; Kumar, Sunil; Singh, Prashant; et al. (Indian Journal of Agroforestry, 2020)
The present study was conducted at ICAR-Central Agroforestry Research Institute, Jhansi to assess soil fertility status of groups of watershed along with control area. Soil samples were collected from three villages (Parasai, Chhatpur and Bachhauni) of watershed site-I of Jhansi district (U.P.), three villages (Shivrampur, Kundar and Dabar) of Tikamgarh district (M.P.) of watershed site-II and two villages (Ganeshgarh and Nayakhera) of Jhansi district (U.P.) as control site. The samples were collected from 0-15 cm soil depth with auger in grid fashion, following standard protocols and assessed for fertility parameters. The soils were slightly (pH: 7.3-7.8) to moderately alkaline (pH: 7.8-8.4). The organic carbon status ranged from low to medium, and available nitrogen (N) was found mostly in low category. The soil available phosphorus (P) was low to medium; available potassium (K) in medium range; and available sulphur (S) in low category. Regarding available micronutrients, boron (B) and zinc (Zn) were in low category, and level of copper (Cu), iron (Fe) and manganese (Mn) were in sufficient range. The assessment of soil fertility in watershed sites revealed that, watershed site-I had better soil fertility status as compared to watershed site-II and control site. Thus, the fertility status data suggests that organic carbon, N, P, S, B and Zn were major soil fertility constraints in the studied watershed areas in Bundelkhand region of semi-arid tropics, India.